Kinetic process of nitridation on the a-sapphire surface - 汤星舟 李书平 康俊勇 陈佳琪 (Journal of semiconductors, 2014)
We established a model to simulate the growth process of nitridation and clarified the inner mechanisms ofnitridation and over-nitridation by combining the kinetic Monte Carlo and molecular dynamics methods. Supported by reflection high-energy electron diffraction results with growth in an MBE system, the tendency of nitridation on s-sapphire in different conditions was observed and analyzed. The best conditions for nitridation on the a-sapphire surface are found by our simulation.